Adult responses to popular music and inter-generational relations in Britain, c. 1955-1975 - Mitchell, Gillian (Anthem studies in British history., 2019)
'Adult Reactions to Popular Music and Inter-generational Relations in Britain, 1955-1975' challenges stereotypes concerning a post-war 'generation gap', exacerbated by rebellion-inducing popular music styles, by demonstrating the considerable variety which frequently characterized adult responses to the music, whilst also highlighting that the impact of the music on inter-generational relations was more complex than is often assumed. [NP] Utilizing extensive primary evidence, from first-person accounts to newspapers, television programmes, surveys and archive collections, the book adopts a thematic approach, identifying three key arenas of British society in which adult responses to popular music, and the impact of such reactions upon relations between generations, seem particularly revealing and significant. The book examines in detail the place of popular music within family life and Christian churches and their engagement with popular music, particularly within youth clubs. It also explores 'encounters' between the worlds of traditional Variety entertainment and popular music while providing broader perspectives on this most dynamic and turbulent of periods.